2014
DOI: 10.4103/0974-8520.159027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Curcuma longa L. extract to stain various tissue samples for histological studies

Abstract: Background:Curcuma longa L. is a perennial herb and a member of the Zingiberaceae (ginger) family, which is used extensively in foods as well as in Ayurvedic and Chinese systems of medicine. Current researches have focused on its antioxidant, hepatoprotective, anti-inflammatory, anticarcinogenic and antimicrobial properties. Until now, very few studies suggested its role as a histological stain.Aim:To ascertain its efficacy to be used as a counterstain after hematoxylin, to compare it's staining ability with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Results were similar to previous study by Kumar et al ., where turmeric had shown good and comparable staining to eosin for collagen and skeletal muscle fibers. [ 11 ] In our study, also, turmeric has shown comparable staining to eosin in case of muscle fibers. Even striations are well appreciated.…”
Section: Discussionsupporting
confidence: 76%
“…Results were similar to previous study by Kumar et al ., where turmeric had shown good and comparable staining to eosin for collagen and skeletal muscle fibers. [ 11 ] In our study, also, turmeric has shown comparable staining to eosin in case of muscle fibers. Even striations are well appreciated.…”
Section: Discussionsupporting
confidence: 76%
“…Curcuma longa L. is a perennial herb of the Zingiberaceae family. Its rhizomes are well-developed, elliptical or cylindrical, with a diameter of up to 100 cm [1]. Curcuma longa L. is widely distributed in some countries in East Asia, South Asia and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated the use of natural dyes for use in plant as well as animal histological studies and have found satisfactory results in comparison to the synthetic stains used. [245] Despite various shortcomings with the use of natural stains, they can still be sought as an analogous to the conventional stains used. [6] However, continuum of studies using natural dyes in human tissues is very narrow and very minimal data in this regard is available in the literature.…”
Section: Introductionmentioning
confidence: 99%